PENERAPAN MONITORING KEAMANAN GEDUNG GEREJA GKI JEMAAT LEMBAH YORDAN BERBASIS ANDROID - Mingsep Rante Sampebua; Jonathan k. Wororomi (LPPM Uncen, 2023)
One of the problems at GKI Lembah Jordan Congregation is monitoring the security of the church building's environment which is often visited by irresponsible people. This is done to avoid various crimes such as destroying church facilities, scribbling on church walls, stealing church assets, and so on. The purpose of this service activity is to provide training to the multimedia team and church guards at the GKI Lembah Jordan congregation, so they can understand how to use environmental security monitoring of church buildings with Android-based Smart Home Camera C6N technology devices. The result of the service activity is that the multimedia team and church guards can monitor the security of the church building environment in real time from a distance using a smartphone.Keywords: Android; Camera C6N; Congregation; Security; Lembah Yordan; Monitoring